Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Increased Potassium Content and Expression of Genes Encoding Potassium Channels in Lycium barbarum - Zhang, Haoqiang; Wei, Suzhen; Hu, Wentao; Xiao, Longmin; Tang, Ming (Frontiers in Plant Science, 2017)
Potassium in plants accounts for up to 10% dry weight, and participates in different physiological processes. Under drought stress, plant requires more potassium but potassium availability in soil solutes is lowered by decreased soil water content. Forming symbiosis with arbuscular mycorrhizal (AM) fungi not only enlarges exploration range of plant for nutrient and water in soil, but also improves plant drought tolerance. However, the regulation of AM fungi on plant root potassium uptake and translocation from root to shoot was less reported. In current study, the effect of an AM fungus (Rhizophagus irregularis), potassium application (0 mM, 2 mM and 8 mM), and drought stress (30% field capacity) on Lycium barbarum growth and potassium status was evaluated. Ten weeks after inoculation, R. irregularis colonized more than 58% root of L. barbarum seedlings, and improved plant growth as well as potassium content. Potassium application increased colonization rate of R. irregularis, plant growth, potassium content, and decreased root/shoot ratio. Drought stress increased colonization rate of R. irregularis and potassium content. Expression of two putative potassium channel genes in root, LbKT1 and LbSKOR, was positively correlated with potassium content in root and leaves, as well as the colonization rate of R. irregularis. The increased L. barbarum growth, potassium content and genes expression, especially under drought stress, suggested that R. irregularis could improve L. barbarum root potassium uptake and translocation from root to shoot. Whether AM fungi could form a specific mycorrhizal pathway for plant potassium uptake deserves further studies.